Affirmative Legal Measures for Persons with Disabilities: Ensuring Accessibility in General Elections in Indonesia - Bintang Aspanu Nebuchadnezzer, (Semarang State University Undergraduate Law and Society Review, 2025)
This study examines the accessibility rights of persons with disabilities in the context of general elections in Indonesia based on national regulations and their implementation. Although Law Number 8 of 2016 and KPU Regulation Number 25 of 2023 have established inclusive political rights for persons with disabilities, challenges remain in practice, such as insufficient facilities and assistive devices at polling stations (TPS). Survey findings and election monitoring reports reveal a significant gap between regulations and their implementation, especially in providing adequate accessibility. This article also highlights the importance of affirmative legal policies, involvement of disability organizations, and stricter oversight to ensure full and equal political participation for persons with disabilities. The study concludes that structured and systematic efforts are needed to guarantee an inclusive democracy that upholds human rights and equality.